The Mobile Banking Application to Boost Service: How the Elderly Consumers’ Perceptions? - Rosa Rilantiana; Roostikasari Nugraheni (JURNAL SOSIAL HUMANIORA (JSH), 2023)
This research aims to examine the factors influencing the decision-making process of older individuals when it comes to using electronic banking services. While technology plays a crucial role in today's society, it may not be enough to reach vulnerable populations, particularly the elderly. The study will utilize the STATA 14.2 program for SEM analysis, employing quantitative analysis to explore decisions related to digital banking applications within a sample of 300 individuals aged over 50 in Surabaya. During the Covid-19 pandemic, digital technology served as an operational tool to mitigate the spread of the virus. However, it is essential to recognize that technology is a long-term investment, even after the pandemic. Elderly users need to be mindful of sudden technological changes and improve their digital literacy. This study underscores the importance of understanding the banking sector when assessing how specific groups, such as the elderly, utilize digital technologies. Moreover, for business continuity, gaining insights into how the elderly utilize banking apps is crucial. It is imperative to implement the necessary support systems and digital infrastructure promptly and effectively to meet the current and future demands